ANALISIS PERFORMANCE SERAT OPTIK SEBAGAI MEDIA TRANSMISI PADA JALUR TRANSMISI LUBUK BASUNG–LUBUK SIKAPING - Riri Yulianti Solfia; Putra Jaya; Yasdinul Huda (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
This study aims to investigate the performance of optical fiber as a transmission medium. This was conducted using the discrepancy modle, which made the comparison between the measured data with the standard used PT.Telkom and ITU-T. Object of this research is the value of attenuation and power link budget. Based on the measured data on each core is core 3,7,9,10,12,15,18,20, and 23 obtained the following values as 0.239 dB / km, 0.238 dB / km, 0.240 dB / km, 0.239 dB / km , 0.236 dB / km, 0.240 dB / km, 0.242 dB / km, 0.233 dB / km, 0.238 dB / km, and the results of calculations on the same cores with each core attenuation is 0.235 dB / km, 0.235 dB / km, 0.235 dB / km, 0.235 dB / km, 0.235 dB / km, 0.235 dB / km, 0.237  dB  /  km,  0.235  dB  /  km,  0.235  dB  /  km,  based  on  the  results  of  calculation, measurement and compared with standard attenuation values are in compliance with standards ITU-T and PT.Telkom because it does not exceed the maximum attenuation is 0.25 dB/km. Analysis performed with comparing the power in receive (Rx) between the results of the calculation of each core with measurement results and instrument sensitivity, but the overall results  of  the  calculation  and  measurement  is  still  at  the  maximum  value  of  threshold sensitivity system is -19 dBm. Key   words :  Core,   Performance,   Attenuation,   Power   Link   Budget,   Rx   Levell